Alternative dispute resolution of shareholder disputes in Hong Kong : institutionalizing its effective use - Mak, Ida Kwan Lun (Cambridge University Press, 2017)
Uses an interdisciplinary and empirical approach to analyze the process of institutionalizing alternative dispute resolution for shareholder disputes in Hong Kong.